The Effect of Digital Marketing and Service Quality on Motorcycle Purchasing Decisions at the Yamaha Padayungan Motor Tasikmalaya Dealers - Nugraha, Adi Kustandi; Paramita, Veronika Santi (Fakultas Ekonomi dan Bisnis, Universitas Jenderal Achmad Yani, 2026)
Competition in the business world is getting tighter, this requires every company to be able to take the right strategic steps to win the competition with competitors. One example is the Yamaha Padayungan Motor Dealership, after being closed for almost 4 years in motorcycle sales, trying to bounce back with more effective and efficient marketing measures to keep up with the times. With the implementation of digital marketing and improving service quality, the dealer strives to have fast and significant sales progress. So that it can restore the reputation of the Yamaha Padayungan Motor dealer back to become one of the Pioneer dealers in Tasikmalaya City. This study aims to find out how to descriptive analysis of digital marketing conditions, service quality and motorcycle purchase decisions, how the influence of digital marketing and service quality on motorcycle purchase decisions at Yamaha Padayungan Motor dealers. This research method uses a quantitative approach with a descriptive method of causality. The data collection technique uses a questionnaire with a Google Form which is distributed to consumers who have bought a motorcycle at a Yamaha Padayungan Motor dealership, with the number of consumers who answered the questionnaire as many as 100 respondents. For the data processing process and analysis, multiple linear regression analysis was used with the help of the SPSS version 26.0 application. The results of this study show that digital marketing and service quality have a positive and significant effect on motorcycle purchase decisions at Yamaha Padayungan Motor dealers.